2017
DOI: 10.1136/bjophthalmol-2017-311328
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics imaging of inherited retinal diseases

Abstract: Adaptive optics (AO) ophthalmoscopy allows for non-invasive retinal phenotyping on a microscopic scale, thereby helping to improve our understanding of retinal diseases. An increasing number of natural history studies and ongoing/planned interventional clinical trials exploit AO ophthalmoscopy both for participant selection, stratification and monitoring treatment safety and efficacy. In this review, we briefly discuss the evolution of AO ophthalmoscopy, recent developments and its application to a broad range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 92 publications
(81 reference statements)
1
58
0
1
Order By: Relevance
“…Further work using more detailed imaging techniques, such as adaptive optics scanning light ophthalmoscopy (AOSLO), may better demonstrate the earliest indicators of any structural progression in ACHM. 17 AOSLO allows visualization of individual rod and cone cells in vivo 18 , 19 and has confirmed the presence of cone photoreceptors in all patients with ACHM, albeit reduced in number compared to the unaffected retina, with a wide range of cone densities, and often a disconnect with SD-OCT appearance. 20 With regard to assessing progression of ACHM with AOSLO, Langlo et al 21 demonstrated that foveal cone structure showed little or no change in their cohort of patients with CNGB3 -ACHM over a follow-up period of 6 to 26 months.…”
Section: Discussionmentioning
confidence: 78%
“…Further work using more detailed imaging techniques, such as adaptive optics scanning light ophthalmoscopy (AOSLO), may better demonstrate the earliest indicators of any structural progression in ACHM. 17 AOSLO allows visualization of individual rod and cone cells in vivo 18 , 19 and has confirmed the presence of cone photoreceptors in all patients with ACHM, albeit reduced in number compared to the unaffected retina, with a wide range of cone densities, and often a disconnect with SD-OCT appearance. 20 With regard to assessing progression of ACHM with AOSLO, Langlo et al 21 demonstrated that foveal cone structure showed little or no change in their cohort of patients with CNGB3 -ACHM over a follow-up period of 6 to 26 months.…”
Section: Discussionmentioning
confidence: 78%
“…14 In the same study, Jacobson and associates identified outer nuclear layer thinning over the fovea and decreased intensity of the EZ reflectivity. 14 Further evaluation of retinal structure with adaptive optics ophthalmoscopy may be of value, 37 in order to further elucidate the photoreceptor structure in these patients at a cellular level; however, this will likely be challenging in many patients owing to poor fixation/nystagmus, keratoconus, and early-onset cataract.…”
Section: Discussionmentioning
confidence: 99%
“…24 Adaptive optic retinal imaging in human CNGB3 and CNGA3 achromatopsia cases has shown a slow decline in foveal cone density and changes in cone reflectivity throughout life. 25 In both the cpfl10 mouse and human cases, cones survive long enough to provide a therapeutic window for treatment.…”
Section: Discussionmentioning
confidence: 99%